2010
DOI: 10.1002/cncr.25429
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary use of perioperative cisplatin‐based chemotherapy in patients with muscle‐invasive bladder cancer

Abstract: BACKGROUND: Level I evidence indicates that neoadjuvant cisplatin-based chemotherapy, in combination with radical cystectomy (RC), is associated with a significant survival advantage for patients with muscle-invasive bladder cancer. Despite this, neoadjuvant chemotherapy is not uniformly used. Our objective was to determine the patterns of utilization of neoadjuvant chemotherapy in patients undergoing RC for muscle invasive bladder cancer in a contemporary cohort in a tertiary care center. METHODS: A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 50 publications
2
65
0
5
Order By: Relevance
“…18 Similar to previous reports, 15,19 in the 46% of patients in this series who were ineligible for NAC, the primary reason was inadequate renal function.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…18 Similar to previous reports, 15,19 in the 46% of patients in this series who were ineligible for NAC, the primary reason was inadequate renal function.…”
Section: Discussionsupporting
confidence: 82%
“…4 While earlier studies have shown that only 1% to 5% of bladder cancer patients received NAC, there does appear to be a small increase in the use of NAC since 2003, with rates increasing to 12% to 19%. 9,15,16 In this series, 91/113 (80%) of potentially eligible patients received NAC (Fig. 1).…”
Section: Discussionmentioning
confidence: 81%
“…Unfortunately, the use of neoadjuvant chemotherapy in patients undergoing cystectomy is limited, with as few as 17% of patients with T2 or greater disease receiving treatment, even at academic centers. 30,31 These low rates of use can be partially explained by patient comorbidity, especially renal insufficiency, and poor performance status. Some experts advocate for early cystectomy in patients who are unable to tolerate platinum-based chemotherapy regimens, although this remains an area of controversy.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…In a study reported by Raj and colleagues, among 145 patients who underwent RC for preoperative clinical stage ≥T2 disease, where only 17% received cisplatin-based NC, the main reasons cited for lack of use were age, comorbidities, concerns over toxicity and the modest nature of benefit. 26 This latter point may particularly be an issue in patients with clinically staged, cT2 disease where the relative benefit from NC appears smaller compared to that of T3 or T4a disease, but nevertheless there is still a 5% OS benefit at 5 years. Another reason to offer NC to patients with cT2 disease is that a significant number of patients are upstaged at the time of RC.…”
Section: Patient Selection For Ncmentioning
confidence: 99%